Monitoring xenotransplant recipients for infection by PERV - Herring, Chris; Cunningham, Deirdre A; Whittam, Alison J; Fernández-Suárez, Xosé M; Langford, Gillian A (Clinical biochemistry, 2001)
Objectives: Concerns have been raised over the possibility of transmission of porcine endogenous retrovirus ( PERV) to porcine xenograft recipients. Methods: To help assess this risk, diagnostic assays capable of detection of an active, latent or cleared PERV infection, and the presence of pig cell microchimerism have been developed by a number of groups. Retrospective studies of patients exposed to living pig tissues have been performed using these assays to look for evidence of cross species transmission. Results: To date no evidence of PERV infection has been found in studies of humans exposed to pig tissues, despite evidence of long lived microchimerism. Conclusions: These data suggest that PERV infection has not occurred in a clinical setting. However, as infection has been seen in a small animal model further investigation of the risk from PERV is warranted.